Physical examination of surgical short cases / Yahya Mohd Aripin, Kadhim Jawad Obaid and Mohd Zamrin Dimon - Mohd Aripin, Yahya; Obaid, Kadhim Jawad; Dimon, Mohd Zamrin
Physical Examination of Surgical Short Cases is the initial clinical assessment on surgical patients, with the purpose of determining the nature and locoregional extension of a lesion or a diseased organ. Typically, the assessment involves performing a set of clinical tests in order to elicit specific clinical signs. At the end of this 5 to 10 minutes assessment, the provisional and differential diagnoses of the lesion are expected to be known. Laboratory investigations and/or imaging may or may not be necessary for confirmation of the diagnosis. History may be taken retrospectively, if further assessment about the lesion or disease is needed. This book emphasizes on proper technique of examination and put forward sequence of examination steps. The descriptions of techniques in this book are simplified, to be more of "how to do it", and steps of examination are in point form, so that it is easily read and readily applicable on patients. Nine topics of physical examination are included in this book. These are the examinations that cover all common diseases seen in surgical outpatient clinic and inpatients. Couple with general examination and systemic examinations, which can be found in other medical textbooks, we believe are adequate for undergraduates to have full coverage of clinical assessment on common diseases of surgical importance.